Production of Sustainable Aviation Fuels in Petroleum Refineries: Evaluation of New Bio-Refinery Concepts - Tanzil, Abid H; Brandt, Kristin; Zhang, Xiao; Wolcott, Michael; Stockle, Claudio; Garcia-Perez, Manuel (Frontiers in Energy Research, 2021)
The potential for petroleum refineries (PRs) to integrate sustainable aviation fuel (SAF) technologies is manifold, unlike with other existing industrial infrastructures that lack such technical similarities. A midsize PR with a crude oil capacity of 120,000 barrels per day was analyzed in this study to determine the feasibility of integrating five well-known lignocellulosic SAF technologies, namely, Virent’s BioForming (VB), alcohol to jet (ATJ), direct sugar to hydrocarbon (DSHC), fast pyrolysis (FP), and gasification and Fischer–Tropsch (GFT) methods, as well as one novel concept referred to as integrated carbonization-gasification-Fischer–Tropsch (ICGFT). The following three integrated scenarios were studied to derive the costs and environmental impact reductions: sharing of infrastructures from outside battery limits (OSBL), co-processing of SAF technology-derived intermediates with PR-derived gas oil inside battery limits (ISBL) and repurposing of an idle or shutdown PR. Sharing OSBL infrastructures resulted in reductions of the minimum fuel selling price (MFSP) by 3–14% relative to the corresponding standalone cases. Co-processing of intermediate products such as VB-derived long chain hydrocarbons, ATJ-derived ethanol, DSHC-derived farnesene, pyrolysis-derived bio-oil, and GFT-derived FT products reduced the MFSP by 10–19% from corresponding standalone cases. Moreover, repurposing scenarios reduced the costs by 16–34%. Greenhouse gas (GHG) estimations showed that 17 of 21 integrated scenarios resulted in GHG savings (7–92%). Lignocellulosic SAF technologies are limited by low fuel yields, which are governed by the high oxygen content of the feedstock. However, ICGFT was found to be advantageous in terms of fuel production at a maximized fuel yield.